MEASURING THE EFFECTIVENESS OF MARKETING INVESTMENTS USING THE METHOD OF SNEDECOR’S F DISTRIBUTION - Vojvodic, Nikola (Journal of process management and new technologies, 2016)
The environment in which insurance companies operate is all the more complex and turbulent which requires a systemic approach to business and adaptation to the constant changes on the insurance market. In order to create or maintain the competitive advantage it is necessary to study marketing in insurance as a new, scientific, meaningful, technologically more advanced and profitable approach in this field. It includes applying tools of the marketing mix and implementing the activity of analysis of: environment (external and internal), formulating the strategy of market performance, implementation of the strategy as well as its estimate and control, promotion and adequate channels of insurance products distribution.